2021
DOI: 10.4110/in.2021.21.e30
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 Promotes the Epithelial-Mesenchymal Transition-Induced Cervical Cancer Progression

Abstract: High expression of mitofusin-2 (MFN2), a mitochondrial fusion protein, has been frequently associated with poor prognosis of patients with cervical cancer. Here, we aimed to identify the function of MFN2 in cervical cancer to understand its influence on disease prognosis. To this end, from cervical adenocarcinoma, we performed an MTT assay and quantitative RT-PCR (qRT-PCR) analysis to assess the effects of MFN2 on the proliferation and of HeLa cells. Then, colony-formation ability and tumorigenesis were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…With the advancement of precision tumour therapy, new biological markers are urgently needed for definitive diagnosis and precise treatment [ 29 , 30 ].In this study, analysis of the TCGA database clarified that MFN2 was significantly low expressed in renal clear cell carcinoma relative to normal kidney tissue.It has been shown that MFN2 shows low expression in breast cancer, and MFN2 can inhibit mTORC2 expression and inhibit tumor growthby binding to mTORC2 domain HR1 [ 31 ] .A study on gastric cancer showed that the expression of MFN2 was lower than that in normal gastric mucosa tissue, and after overexpressed MFN2, it downregulated the expression of MMP-2 and MMP-9 attenuated the invasion and migration ability of cancer cells by inhibiting PI3K/Akt signaling and inhibited tumor progression [ 32 ].MFN2 regulates mitochondrial fusion / division in cells in thyroid cancer and affects cellular metabolism, which regulates EMT in tumors through induction of the AKT signaling pathway [ 33 ].In ovarian cancer, increased expression of MFN2 triggers AMPK, promotes autophagy, reduces ROS, and suppresses ovarian cancer progression through downregulation of p-mTOR and p-ERK axis [ 34 ] .MFN2 is highly expressed in cervical cancer, and the knockout of MFN2 can significantly inhibit the proliferation and EMT of cervical cancer cells, becoming a new target for the treatment of tumors [ 35 ].MFN2 expression was significantly downregulated in bladder cancer cells, and it can inhibit the Wnt/β-catenin signaling pathway to inhibit tumor progression through [ 36 ].MFN2 induces autophagy and promotes apoptotic in pancreatic cancer cells by inhibiting the PI3K/Akt/mTOR signaling pathway in pancreatic cancer [ 37 ].However, how MFN2 is expressed and how it functions in renal clear cell carcinoma is unclear and requires further study.In our study, MFN2 showed low expression and correlated with worse pathological stage, T-stage, histological grade, and M-stage.In addition, we found that low expression of MFN2 was associated with poorer OS, DSS and PFI, and univariate and multifactorial COX regression analyses showed that MFN2 expression was an important independent prognostic factor for renal clear cell carcinoma. Taken together, MFN2 could be a new molecular candidate to treat renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of precision tumour therapy, new biological markers are urgently needed for definitive diagnosis and precise treatment [ 29 , 30 ].In this study, analysis of the TCGA database clarified that MFN2 was significantly low expressed in renal clear cell carcinoma relative to normal kidney tissue.It has been shown that MFN2 shows low expression in breast cancer, and MFN2 can inhibit mTORC2 expression and inhibit tumor growthby binding to mTORC2 domain HR1 [ 31 ] .A study on gastric cancer showed that the expression of MFN2 was lower than that in normal gastric mucosa tissue, and after overexpressed MFN2, it downregulated the expression of MMP-2 and MMP-9 attenuated the invasion and migration ability of cancer cells by inhibiting PI3K/Akt signaling and inhibited tumor progression [ 32 ].MFN2 regulates mitochondrial fusion / division in cells in thyroid cancer and affects cellular metabolism, which regulates EMT in tumors through induction of the AKT signaling pathway [ 33 ].In ovarian cancer, increased expression of MFN2 triggers AMPK, promotes autophagy, reduces ROS, and suppresses ovarian cancer progression through downregulation of p-mTOR and p-ERK axis [ 34 ] .MFN2 is highly expressed in cervical cancer, and the knockout of MFN2 can significantly inhibit the proliferation and EMT of cervical cancer cells, becoming a new target for the treatment of tumors [ 35 ].MFN2 expression was significantly downregulated in bladder cancer cells, and it can inhibit the Wnt/β-catenin signaling pathway to inhibit tumor progression through [ 36 ].MFN2 induces autophagy and promotes apoptotic in pancreatic cancer cells by inhibiting the PI3K/Akt/mTOR signaling pathway in pancreatic cancer [ 37 ].However, how MFN2 is expressed and how it functions in renal clear cell carcinoma is unclear and requires further study.In our study, MFN2 showed low expression and correlated with worse pathological stage, T-stage, histological grade, and M-stage.In addition, we found that low expression of MFN2 was associated with poorer OS, DSS and PFI, and univariate and multifactorial COX regression analyses showed that MFN2 expression was an important independent prognostic factor for renal clear cell carcinoma. Taken together, MFN2 could be a new molecular candidate to treat renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, immunohistochemical markers of apoptosis p53 and human epidermal growth factor receptor 2 protein levels were evaluated by as potential prognostic factors in cervical cancer associated with a poor prognosis [97]. At present, molecular, biochemical and genetic aspects of cervical carcinogenesis continue to be investigated [98,99]. PI3K/Akt, Wnt/β-catenin, ERK/MAPK, NF-κB, YY1, AP-1, JAK/STAT and CXCL12/CXCR4 signaling pathways have a significant role in the cervical cancerogenesis in HPV-infected individuals [98].…”
Section: Discussionmentioning
confidence: 99%
“…Mfns serve as key proteins for the induction of mitochondrial fusion that are important for mitochondrial dynamics as well as mitochondrial function and homeostasis [ 147 ]. Therefore, the onset and development of many diseases are closely associated with Mfns, such as cancer, neurological diseases, obesity, and vascular diseases [ 148 152 ]. Interestingly, recent discoveries have revealed that several reproductive diseases are also closely associated with Mfns, such as asthenozoospermia, polycystic ovary syndrome (PCOS), and gestational diabetes mellitus (GDM) (Fig.…”
Section: Mfns In Reproductive Diseasesmentioning
confidence: 99%